Arabidopsis CHROMOSOME TRANSMISSION FIDELITY 7 (AtCTF7/ECO1) is required for DNA repair, mitosis and meiosis - Bolaños Villegas, Pablo Alberto (2013)
artículo -- Universidad de Costa Rica. Escuela de Agronomía, 2013.